The impact of process variables and wear characteristics on the cutting tool performance using Finite Element Analysis - Jiang, Xiaoheng (Cranfield University, 2016)
The frequent failure of cutting tool in the cutting process may cause a huge loss of money and time especially for hard to machine materials such as titanium alloys. Thus this study is mainly focused on the impact of wear characteristics and process variables on the cutting tool which is ignored by most of researchers. A thermo-mechanical finite element model of orthogonal metal cutting with segment chip formation is presented. This model can be used to predict the process performance in the form of cutting force, temperature distribution and stress distribution as a function of process parameters. Ls-dyna is adopted as the finite element package due to its ability in solving dynamic problems. Ti-6Al-4V is the workpiece material due to its excellent physical property and very hard to machine. This thesis uses the Johnson-Cook constitutive model to represent the flow stress of workpiece material and the Johnson-Cook damage model to simulate the failure of the workpiece elements. The impacts of process variables and tool wear are investigated through changing the value of the variables and tool geometry. It is found that flank wear length has a linear relationship with the cutting force which is useful for predicting the cutting tool performance. Increasing the crater wear will in some degree diminishes the cutting force and temperature. A chip breakage will also happen in some cases of crater wear. Through these findings, the relationship between flank wear and cutting power is established which can be used as the guidance in the workshop for changing the tools. The distribution of temperature and stress on the cutting tool in different cutting conditions can be adopted to predict the most possible position forming cutting tool wear.
Keywords: FEM; cutting temperature; Ls-dyna; Ti-6Al-4V; flank wear; crater wear; cutting power